High and stable performance under adverse traffic patterns of tori-connected torus network - Rahman, M.M. Hafizur; Sato, Yukinori; Inoguchi, Yasushi (Elsevier Limited, 2013)
A Tori connected Torus Network (TTN) is a scalable interconnection network constructed from hierarchically interconnected 2D-torus networks. Static network performance of the fixed size TTN and dynamic communication performance under very common traffic patterns have been evaluated. However, a generalized study of static network performance of TTN with any size and its dynamic communication performance under adverse traffic patterns has not been evaluated yet. In this paper, we show that the TTN with any size possesses several attractive features, including constant node degree, small diameter, low cost, small average distance, moderate bisection width, and high fault tolerant performance than that of other networks like fixed size TTN. We further evaluate the dynamic communication performance of TTN, and compare it with hierarchical TESH & MH3DT and conventional mesh & torus networks. We found that under adverse traffic patterns, the TTN yields high throughput and low latency, providing better dynamic communication performance compared to TESH, MH3DT, mesh, and torus networks. Also, we found that adverse traffic patterns have stable throughput than uniform traffic in the TTN.